Study about Fungal Glycosidases in Sporothrix Species and Candida albicans - Ortiz-Ramírez, Jorge A.; Cuéllar-Cruz, Mayra; Villagómez-Castro, Julio C.; López-Romero, Everardo (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
The present study highlights about Fungal Glycosidases in Sporothrix Species and Candida albicans. Through the hydrolysis of glycosidic bonds in glycosides, enzymes known as glycoside hydrolases (GHs) take part in a variety of biological activities in fungi and other organisms. They are substantial topics of research in molecular biology and biochemistry and have essential functions in the breakdown of carbohydrates and the building of glycoproteins. Based on amino acid sequence similarities and 3-dimensional structures in the carbohydrate-active enzyme (CAZy), they have been classified in 171 families. Members of some of these families also exhibit the activity of trans-glycosydase or glycosyl transferase (GT), i.e., they create a new glycosidic bond in a substrate instead of breaking it. Fungal glycosidases are important for virulence by aiding tissue adhesion and colonization, nutrition, immune evasion, biofilm formation, toxin release, and antibiotic resistance. Here, we review fungal glycosidases with a particular emphasis on Sporothrix species and C. albicans, two well-recognized human pathogens. Covered issues include a brief account of Sporothrix, sporotrichosis, the different types of glycosidases, their substrates, and mechanism of action, recent advances in their identification and characterization, their potential biotechnological applications, and the limitations and challenges of their study given the rather poor available information. The study approaches will strengthen genetic glycoengineering, as glycosylation/deglycosylation can be used to modulate the efficiency of protein pharmaceuticals, the modification of glycoprotein antibodies by adding or changing the position of some sugars, changing the properties of recombinant proteins, etc. These achievements will impact the areas of biotechnology, biomedicine, and consequently, human health.